The Trypanosomiases 2004
DOI: 10.1079/9780851994758.0113
|View full text |Cite
|
Sign up to set email alerts
|

Tsetse population dynamics.

Abstract: Mosquitoes and tabanids deposit their eggs in water, stable flies and horn flies deposit them in wet dung. Most biting flies, in short, lay their eggs in a moist environment in which their larvae feed and develop. In the tsetse fly (Glossina spp.), by contrast, a single fertilised egg is retained in the uterus during each pregnancy and, when it hatches, the female feeds it until she deposits it as late third instar larva. The larva, which may weigh more than the female which has just deposited it, burrows into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
180
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(188 citation statements)
references
References 63 publications
8
180
0
Order By: Relevance
“…Why metabolic rate should increase following exposure to a relatively low temperature in tsetse adults is not clear, but might contribute to the absence of this species (and G. morsitans) from low temperature areas. Elevated metabolic rates will result in increased use of lipid reserves, lower tolerance of starvation, and increased pressure for foraging, all of which are likely to enhance the chances of mortality (Rajagopal and Bursell, 1966), likely limiting the ability of the flies to survive in low temperature environments (though a lack of pupal development is also important for restricting flies to warmer areas; for reviews, see Hargrove, 2004;Rogers and Robinson, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Why metabolic rate should increase following exposure to a relatively low temperature in tsetse adults is not clear, but might contribute to the absence of this species (and G. morsitans) from low temperature areas. Elevated metabolic rates will result in increased use of lipid reserves, lower tolerance of starvation, and increased pressure for foraging, all of which are likely to enhance the chances of mortality (Rajagopal and Bursell, 1966), likely limiting the ability of the flies to survive in low temperature environments (though a lack of pupal development is also important for restricting flies to warmer areas; for reviews, see Hargrove, 2004;Rogers and Robinson, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, investigations of non-lepidopteran species are likely to provide a rapid way of determining how general previous findings are likely to be. Second, temperature and water availability are important correlates of the distribution of G. pallidipes and play major roles in influencing its population dynamics directly (Hargrove, 2004;Rogers and Robinson, 2004) and indirectly via metabolic rate (Bursell et al, 1974;Bursell and Taylor, 1980;Terblanche et al, 2004). Investigating the mechanistic bases of the responses of flies to their external environment is therefore a significant link in the causal chain of reasoning from environment to population dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Helmuth et al (2002) have shown that in Pacific intertidal mussels Mytilus californianus, tidal regime, wave height and local climate interact such that sites which might otherwise have been considered relatively temperate are associated with greater thermal stresses than apparently much warmer sites. In tsetse, Glossina morsitans and Glossina pallidipes, population dynamic investigations have demonstrated that high temperatures substantially increase daily instantaneous mortality rates (Hargrove 2004). Recent macrophysiological work has shown that a combination of direct high-temperature effects on survival and indirect effects via an increase in foraging-associated risk precipitated by elevated resting metabolic costs at high (but sub-lethal) temperatures are probably the source of the change in mortality rates .…”
Section: Climate Changementioning
confidence: 99%
“…Although several factors may affect the range of vector-borne diseases in the short term, climate change is expected to heavily modify the suitable range of some parasitic diseases such as malaria, bluetongue, and trypanosomosis (Woolhouse 2006, Thornton 2010, Van Dijk et al 2010). Climate change is therefore a key cause in our case study (Table 1) because of the strong effect temperature has on the reproductive success and distribution of tsetse flies and the Trypanosoma parasites (Hargrove 2004, Moore et al 2012. Tsetse pupal development periods decrease with increasing temperatures, and larval production ceases altogether above a certain temperature threshold (Hargrove 2004).…”
Section: Causesmentioning
confidence: 99%
“…These unique conditions therefore create a telecoupled system among international importers and exporters of livestock products. However, because of a changing climate, temperatures are expected to rise to levels that are harmful to tsetse reproduction and survival as well as pathogen development (Hargrove 2004, Moore et al 2012. Recent work has shown that increasing temperatures during the next few decades will substantially reduce the geographic range of one species of the trypanosome parasite in Mozambique ( Fig.…”
Section: Cattle and Trypanosomamentioning
confidence: 99%